USP7 Inhibition Alleviates H2O2-Induced Injury in Chondrocytes via Inhibiting NOX4/NLRP3 Pathway - Liu, Gang; Liu, Qingbai; Yan, Bin; Zhu, Ziqiang; Xu, Yaozeng (Frontiers in Pharmacology, 2021)
As the most common form of arthritis, osteoarthritis (OA) is a very common joint disease which often affects middle-age to elderly people. However, current treatment options for OA are predominantly palliative. So, it is of great importance to better understand the pathological process and explore potential therapeutic approaches. Rat chondrocytes were isolated and exposed to hydrogen peroxide (H2O2) to mimic OA. The effects of H2O2 on ubiquitin-specific protease 7 (USP7) expression, reactive oxygen species (ROS) levels, proliferation, inflammatory cytokine release, and pyropotosis were measured. USP7 was knocked down (KD) or overexpressed to investigate the role of USP7 in OA. Co-Immunoprecipitation (Co-IP) was used to study the interaction between USP7 and NOX4, and NOX4 ubiquitination. NOX4 inhibitor was applied in order to study the involvement of NOX4 in USP7-mediated OA development. USP7 inhibitor was given to OA animals to further investigate the role of USP7 in OA in vivo. H2O2 treatment significantly increased USP7 expression, enhanced ROS levels, and inhibited proliferation in rat chondrocytes. Overexpression of USP7 enhanced pyropotosis, ROS production, IL-1β and IL-18 level, and expression level of NLRP3, GSDMD-N, active Caspase-1, pro-Caspase-1, MMP1, and MMP13, which was abolished by inhibition of ROS. USP7 KD protected rat chondrocytes against H2O2-induced injury. Co-IP results showed that USP7 interacted with NOX4, and USP7 KD enhanced the ubiquitinylation of NOX4. Inhibition of NOX4 blocked the pro-OA effect of USP7. Moreover, given USP7 inhibitor to OA animals suppressed OA in vivo. USP7 inhibited NOX4 ubiquitination for degradation which leads to elevated ROS production. ROS subsequently activates NLPR3 inflammasome, leading to enhanced production of IL-1β and IL-18, GSDMD-dependent pyroptosis, and ECM remodeling. In short, UPS7 contributes to the progression of OA via NOX4/ROS/NLPR3 axis.